Government institutions and infrastructure skills development - Regan, M.; Smith, J.; Love, Peter (Association of Researchers in Construction Management, 2014)
The capacity of state institutions is central to the efficient delivery and management of infrastructure. The paper examines two models for improving the skills of managers in central and line agencies of government for infrastructure procurement and management in emerging economies. The first examines the role of the Public Private Partnership (PPP) unit, a specialist agency equipped with the technical capabilities, transactional experience and budget to provide training and assistance to line agencies for the effective delivery of infrastructure projects. Integrated into this model, and used by several nations, is the use of trained relationship managers to manage service contracts including government commissioned build operate transfer (BOT), outsourcing and concession arrangements. This approach uses relationship management principles whereby the regulatory framework of the contract in matters such as price, quality, service standards, and performance measurement is exercised within the contract. The second model is the Gateway approach to infrastructure project analysis and development. Gateway was initially implemented in the United Kingdom and has been widely adopted in OECD countries over the past decade as an alternative governance framework for public projects that require the participation of multiple government agencies, private advisers, several levels of approvals and close liaison between the executive and political arms of government. Gateway imposes new disciplines on the project procurement process, requires central and line agencies to undertake professional development training and imposes new governance standards for large and complex infrastructure procurement projects. Evidence suggests that Gateway is playing a significant role raising the capacity of public agencies to manage large and complex procurement projects, and improving procurement performance.